Mycobacterium tuberculosis Acquires Limited Genetic Diversity in Prolonged Infections, Reactivations and Transmissions Involving Multiple Hosts - Herranz, Marta; Pole, Ilva; Ozere, Iveta; Chiner-Oms, Álvaro; Martínez-Lirola, Miguel; Pérez-García, Felipe; Gijón, Paloma; Serrano, María Jesús Ruiz; Romero, Laura Clotet; Cuevas, Oscar; Comas, Iñaki; Bouza, Emilio; et al. (Frontiers in Microbiology, 2018)
Background: Mycobacterium tuberculosis (MTB) has limited ability to acquire variability. Analysis of its microevolution might help us to evaluate the pathways followed to acquire greater infective success. Whole-genome sequencing (WGS) in the analysis of the transmission of MTB has elucidated the magnitude of variability in MTB. Analysis of transmission currently depends on the identification of clusters, according to the threshold of variability (<5 SNPs) between isolates. Objective: We evaluated whether the acquisition of variability in MTB, was more frequent in situations which could favour it, namely intrapatient, prolonged infections or reactivations and interpatient, transmissions involving multiple sequential hosts Methods: We used WGS to analyze the accumulation of variability in sequential isolates from prolonged infections or translations from latency to reactivation. We then measured microevolution in transmission clusters with prolonged transmission time, high number of involved cases, simultaneous involvement of latency and active transmission. Results: Intrapatient and interpatient acquisition of variability was limited, within the ranges expected according to the thresholds of variability proposed, even though bursts of variability were observed. Conclusions: The thresholds of variability proposed for MTB seem to be valid in most circumstances, including those theoretically favouring acquisition of variability. Our data point to multifactorial modulation of microevolution, although further studies are necessary to elucidate the factors underlying this modulation.